Titanium Dioxide onto Polyethylene for Water Decontamination - Ponce, S (2009)
This work was partially supported by CONCYTEC (Peru) trough the project contract 169-2006-OAJ and ANPCyT (Argentina) PICT 33973. The authors are in debt with the reviewers for their useful suggestions to improve this paper.